A computational study of yttria-stabilized zirconia: I. Using crystal chemistry to search for the ground state on a glassy energy landscape. (1st April 2017) - Dong, Yanhao; Qi, Liang; Li, Ju; Chen, I-Wei
Abstract: Yttria-stabilized zirconia (YSZ), a ZrO2 -Y2 O3 solid solution that contains a large population of oxygen vacancies, is widely used in energy and industrial applications. Past computational studies correctly predicted the anion diffusivity but not the cation diffusivity, which is important for material processing and stability. One of the challenges lies in identifying a plausible configuration akin to the ground state in a glassy landscape. This is unlikely to come from random sampling of even a very large sample space, but the odds are much improved by incorporating packing preferences revealed by a modest sized configurational library established from empirical potential calculations. Ab initio calculations corroborated these preferences, which prove remarkably robust extending to the fifth cation-oxygen shell about 8 Å away. Yet because of frustration there are still rampant violations of packing preferences and charge neutrality in the ground state, and the approach toward it bears a close analogy to glass relaxations. Fast relaxations proceed by fast oxygen movement around cations, while slow relaxations require slow cation diffusion. The latter is necessarily cooperative because of strong coupling imposed by the long-range packing preferences. Graphical abstract: A facile protocal by incorporating packing preferences from crystal chemistry has been developed to search for the low-energy configurations on a glassy energy landscape of doped zirconia. Image